High-cycle fatigue behavior of high-speed blanked 5754 aluminum sheets - Lisa Winter; Sven Winter; Verena Psyk; Rico Drehmann; Thomas Lampke (Journal of Materials Research and Technology)
Considering the production of sheet metal parts, high-speed blanking (HSB) is an economically and ecologically relevant alternative to processes such as conventional or fine blanking. Depending on the material and process parameters, the microstructure is significantly affected due to the induced deformation. As the resulting HSB surfaces are characterized by high hardness and a high geometrical accuracy, there is a high potential for producing blanked surfaces, which can be used directly as functional surfaces without further post-processing steps. Besides surface quality, fatigue properties are often relevant for technical applications. However, the fatigue resistance of HSB surfaces has rarely been the focus of scientific research.In this study, the influence of the blanking speed on the high-cycle fatigue behavior of a 5754 aluminum sheet is investigated. A high-speed blanked condition is compared to a conventionally blanked one. A wire electrical discharge machined (EDM) surface serve as non-blanked material reference. Surface roughness, residual stresses, as well as microstructure and hardness are examined besides the fatigue strength and crack initiation sites. The investigation proves a pronounced influence of the blanking speed on the surface quality and microstructural and mechanical properties. The high-speed blanked surface exhibits an increased fatigue strength and a significantly decreased scatter of fatigue life. This can be explained by the roughness, nearly halved, when compared to the conventionally blanked one, as primarily influencing factor. The residual stress state seems to play only a minor role with regard to the overall fatigue resistance and failure mechanisms of blanked surfaces.